2016
DOI: 10.1186/s40792-016-0224-8
|View full text |Cite
|
Sign up to set email alerts
|

Surgical approach to a left ventricular myxoma guided by transesophageal and epicardial dual-view echocardiography: a case report

Abstract: BackgroundLeft ventricular myxoma is a rare benign cardiac neoplasm. Surgical excision is the treatment of choice, and complete removal is mandatory to prevent late recurrence.Case presentationHere, we report a case of myxoma originating from the anterolateral wall of the left ventricle with a very short stalk. Accordingly, the transaortic and transmitral approaches were considered inadequate; therefore, a transventricular approach was adopted. To minimize the incidence of complications associated with a left … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…Through TTE, Qin W et al [ 12 ] observed a LV myxoma attached at the base of the anterolateral papillary muscle in a patient with no history of syncope, palpitation, or dyspnea. Under the guidance of transesophageal echocardiography, Hamasaki A et al [ 13 ] successfully resected the myxoma originating from the left ventricular wall. Transesophageal echocardiography (TEE) can provide more accuracy in the diagnosis of LV myxoma than TTE especially for the detailed information such as the morphology of the mass.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Through TTE, Qin W et al [ 12 ] observed a LV myxoma attached at the base of the anterolateral papillary muscle in a patient with no history of syncope, palpitation, or dyspnea. Under the guidance of transesophageal echocardiography, Hamasaki A et al [ 13 ] successfully resected the myxoma originating from the left ventricular wall. Transesophageal echocardiography (TEE) can provide more accuracy in the diagnosis of LV myxoma than TTE especially for the detailed information such as the morphology of the mass.…”
Section: Discussionmentioning
confidence: 99%
“…The TEE features of left ventricular myxoma present as a pedunculated, homogeneous, and mobile mass, which could stem from any part of the left ventricle. [ 13 , 14 , 15 ] During systole, the mass could protrude into the LVOT, leading to the obstruction of LVOT. Mitral valve prolapse and mild mitral regurgitation may be caused by the mass attached to the anterior lobe of the mitral valve.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation